Prevailing Status of Agricultural Trade between India and European Union - Yeligar, Sharath; Kumar, Shiv; Venkatesh, P.; Kingsly, I.; Nain, Manjeet Singh; Paul, R. K.; Madhurima, U. (Indian Journal of Extension Education, 2022)
This study analysed the current scenario of India-EU trade, composition of trade, growth and instability of agricultural commodities during the period 1997-98 to 2021-22. India’s agricultural export to the EU was US $ 4.7 billion and imported US $ 1.3 billion from the EU in 2021-22. Netherlands, Italy and Germany were three most important EU members for Indian agricultural trade. India mainly exported fishes and marine products, coffee, tea, meat, spices and cotton to the EU. Vegetable oil, raw hides, skin and leather and animal fodder were imported by India from the EU. Compound Annual Growth Rate (CAGR) and Cuddy-Della Valle Index (CDVI) for instability indicated that the total trade between India and the EU have increased consistently with annual growth rate of 6.59 per cent and instability value of 13.97. This provides impetus to policymakers to establish close trade links with counterparts of EU.
Keywords: EU; Agricultural trade; CAGR; CDVI; FTA; International trade